2016
DOI: 10.1155/2016/7481323
|View full text |Cite
|
Sign up to set email alerts
|

Primary Investigation for the Mechanism of Biatractylolide from Atractylodis Macrocephalae Rhizoma as an Acetylcholinesterase Inhibitor

Abstract: Biatractylolide was isolated from ethyl acetate extract of dried Atractylodis Macrocephalae Rhizoma root by multistep chromatographic processing. Structure of biatractylolide was confirmed by 1H-NMR and 13C-NMR. The IC50 on acetylcholinesterase (AChE) activity was 6.5458 μg/mL when the control IC50 value of huperzine A was 0.0192 μg/mL. Molecular Docking Software (MOE) was used to discover molecular sites of action between biatractylolide and AChE protein by regular molecular docking approaches. Moreover, biat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
(25 reference statements)
1
5
0
Order By: Relevance
“…Our previous study confirmed that biatractylolide has a significant effect on reducing the activity of AChE in the brain and improving the memory ability of mouse dementia induced by aluminum trichloride [ 18 ]; moreover, biatractylolide can significantly reduce cholinesterase activity in model rats and improve the behavior and memory of AD model rats induced by A β 1−40 [ 19 ]. Importantly, biatractylolide can inhibit the enzyme activity of AChE and downregulate the expression of AChE in a dose-dependent manner, which has been confirmed in our previous study [ 20 ]. However, the specific mechanisms of biatractylolide are not well understood, and there are no reports about protective effect of biatractylolide currently.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our previous study confirmed that biatractylolide has a significant effect on reducing the activity of AChE in the brain and improving the memory ability of mouse dementia induced by aluminum trichloride [ 18 ]; moreover, biatractylolide can significantly reduce cholinesterase activity in model rats and improve the behavior and memory of AD model rats induced by A β 1−40 [ 19 ]. Importantly, biatractylolide can inhibit the enzyme activity of AChE and downregulate the expression of AChE in a dose-dependent manner, which has been confirmed in our previous study [ 20 ]. However, the specific mechanisms of biatractylolide are not well understood, and there are no reports about protective effect of biatractylolide currently.…”
Section: Introductionsupporting
confidence: 83%
“…Biatractylolide was isolated from the ethyl acetate extract of Atractylodes macrocephala by multistep chromatographic processing [ 20 ] ( Figure 1 ). Glutamate and DMSO were purchased from Sigma Chemicals (USA).…”
Section: Methodsmentioning
confidence: 99%
“…This small molecule has a symmetrical structure containing a novel double sesquiterpene ester. Xie et al (2016) showed that biatractylolide (C30) had a significant effect on inhibiting the activity of AChE in the brain and improved the memory ability of dementia mouse induced by aluminum trichlo-ride. The IC50 values of inhibiting AChE activity is 6.55 µM and its molecular mechanisms includes not only binding to AChE but also reducing AChE expression by inhibiting the activity of glycogen synthase kinase (GSK) 3.…”
Section: Non-alkaloidsmentioning
confidence: 99%
“…The underlying mechanism is an increased expression of PP1 and PP2A, increased phosphorylation of PI3K (p85) and Akt (Ser473) and decreased phosphorylation of GSK3β (tyr216), leading to a reduced level of tau phosphorylation (Liu et al, 2014). Xie et al (2016) demonstrated that biatractylolide (C30) could strongly inhibit AChE activity with an IC50 value of 6.5458 µM. The underlying molecular mechanisms are not only binding to AChE but also reduced AChE expression by inhibition of GSK3 activity.…”
Section: Terpenoidsmentioning
confidence: 99%
“…It could significantly reduce acetylcholinesterase activity in a rat AD model induced by Aβ 1-40 and improve behavior and memory. Therefore, BD showed promising potential to be an effective anti-AD drug [ 44 ].…”
Section: Introductionmentioning
confidence: 99%